Faktor Risiko Tuberkulosis Paru pada Masyarakat di Wilayah Kerja Puskesmas Bambu Apus Kota Tangerang Selatan - Alnur, Rony Darmawansyah; Pangestika, Rismawati (UHAMKA Press, 2018)
ABSTRACT Pulmonary tuberculosis is a contagious disease that is still a problem in the world of health until now. Pulmonary tuberculosis attacks the lungs caused by Mycrobacterium tuberculosis. Indonesia is included in a country with a high burden of tuberculosis, ranking 4th as a contributor to tuberculosis after India, China and South Africa.This study aims to determine internal risk factors that can cause pulmonary tuberculosis in the Dhuafa population. This type of research is analytical with a case control Study. The sample study was divided into case and control samples totaling 30 people with pulmonary tuberculosis and 30 people non-pulmonary tuberculosis. Univariate data were analyzed descriptively and bivariate data were analyzed by Chi-Square test with a 95% confidence level. The results of this studied showed that the risk factors that was the caused of the incidence of pulmonary tuberculosis in the work area of ??Bambu Apus Health Center were a household contact with patient pulmonary tuberculosis. (OR: 3.5; 95% CI: 1.112-11,017; p = 0.028) and habit of smoking family at home (OR: 4,333; 95% CI: 1,203-15,605; p = 0,020). The education level and occupancy density were variables that have no relationship with the incidence of pulmonary tuberculosis in the work area of ??Bambu Apus Health Center. Keywords: Pulmonary Tuberculosis, Risk Factors, Dhuafa